2019
DOI: 10.1001/jamanetworkopen.2019.0168
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated With Acute Pain Estimation, Postoperative Pain Resolution, Opioid Cessation, and Recovery

Abstract: Key Points Question Which prospectively assessed descriptor of the acute pain trajectory in the first 10 days after surgery best estimates the likelihood of remote pain resolution, opioid cessation, and patient-reported complete recovery after surgery? Findings In this secondary analysis of a randomized clinical trial of 422 patients, the worst surgical-site pain intensity over the last 24 hours reported on postoperative day 10 appeared to be the best predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 32 publications
4
90
2
3
Order By: Relevance
“…In our study, female patients were found to have higher baseline pain scores than males after major surgery, consistent with some prior studies 4 6 18. However, the sex difference in the postoperative pain intensity and analgesic consumption remained controversial in previous literature.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, female patients were found to have higher baseline pain scores than males after major surgery, consistent with some prior studies 4 6 18. However, the sex difference in the postoperative pain intensity and analgesic consumption remained controversial in previous literature.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, analyses for temporal domain of pain revealed a meaningful link between psychosocial modulators of postoperative pain and pain chronification 14. A variety of analytical methods have been used to assess the pain trajectory in previous studies, including latent curve model,9 13 14 25 Bayesian change-point model,25 and cluster analysis for trajectory classification 10 12 16–18. Compared with change-point model and cluster analysis, latent curve model is useful in distinguishing between pain intensity and pain resolution and identifying potential influential factors for these two important parameters of pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a metaanalysis of 29 993 patients who had undergone total knee arthroplasty that exclusively examined preoperative risk factors, preoperative pain was most commonly signi cantly associated with persistent postsurgical pain. 30 The present study demonstrated that the VAS scores before surgery and at 7 days after surgery were signi cantly higher in the chronic pain group than in the nonchronic pain group. Compared with the patients without early POCD, the patients who developed POCD had signi cantly higher VAS scores 3 days after surgery and more often requested additional opioids as rescue analgesia postoperatively.…”
Section: Discussionsupporting
confidence: 47%
“…Considering its apparent reliability as a pain sensitivity biomarker, as well as its ease of obtainment, 516 pain-free PAF holds real promise as a pain management and prophylaxis tool. This may be especially 517 true in cases of planned surgery, where post-operative pain sensitivity is consistently found to be an 518 important risk factor for chronic pain development (Hah et al, 2019). For example, identification of high 519 pain sensitivity with PAF could be used to inform clinician decision making about surgical alternatives.…”
Section: Sensorimotor Paf Can Identify the Most Pain Sensitive Indivimentioning
confidence: 99%